2021
DOI: 10.2174/1874944502114010257
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge of Female Students Regarding the Human Papilloma Virus and Vaccines at a Selected University in South Africa

Abstract: Background: The Human Papillomavirus (HPV) is one of the viruses that causes high mortality rates worldwide, and if not detected and treated early, it may lead to fatal complications such as cervical cancer and breast cancer. Purpose: The aim of this study was to determine the knowledge of female students regarding the Human Papillomavirus (HPV) and its vaccines at a selected University in the Limpopo Province, South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…There have been calls to expand the reach of the South African HPV vaccination programme given the unique epidemiology of HPV infection and co-burden of other sexually transmitted infections (including chlamydia, genital herpes, gonorrhea, mycoplasma genitalium, and trichomoniasis) among AGYW >15 years of age (33). Several studies (34)(35)(36)(37) conducted among AGYW >15 years in South African universities either prior to, or following the nationwide roll-out of the HPV vaccination programme have generally reported suboptimal levels of knowledge about HPV, cervical cancer, and the HPV vaccine within this population, which contributes to low-risk perceptions, and risky sexual behaviors and practices. Despite this, female university students consistently demonstrate high levels of HPV vaccine acceptance and willingness to vaccinate if the HPV vaccine were made available to them (34)(35)(36)(37).…”
Section: Supply-side Determinants Of Programme Performancementioning
confidence: 99%
See 1 more Smart Citation
“…There have been calls to expand the reach of the South African HPV vaccination programme given the unique epidemiology of HPV infection and co-burden of other sexually transmitted infections (including chlamydia, genital herpes, gonorrhea, mycoplasma genitalium, and trichomoniasis) among AGYW >15 years of age (33). Several studies (34)(35)(36)(37) conducted among AGYW >15 years in South African universities either prior to, or following the nationwide roll-out of the HPV vaccination programme have generally reported suboptimal levels of knowledge about HPV, cervical cancer, and the HPV vaccine within this population, which contributes to low-risk perceptions, and risky sexual behaviors and practices. Despite this, female university students consistently demonstrate high levels of HPV vaccine acceptance and willingness to vaccinate if the HPV vaccine were made available to them (34)(35)(36)(37).…”
Section: Supply-side Determinants Of Programme Performancementioning
confidence: 99%
“…Several studies (34)(35)(36)(37) conducted among AGYW >15 years in South African universities either prior to, or following the nationwide roll-out of the HPV vaccination programme have generally reported suboptimal levels of knowledge about HPV, cervical cancer, and the HPV vaccine within this population, which contributes to low-risk perceptions, and risky sexual behaviors and practices. Despite this, female university students consistently demonstrate high levels of HPV vaccine acceptance and willingness to vaccinate if the HPV vaccine were made available to them (34)(35)(36)(37). The increased risk of HPV infection makes AGYW >15 years good candidates for targeted interventions aimed at accelerating the prevention of new cervical cancer cases while the observed positive attitude to the HPV vaccine could suggest optimal coverage rates should the vaccination programme be extended to include this population.…”
Section: Supply-side Determinants Of Programme Performancementioning
confidence: 99%
“…This is relatively high and consistent with the 83.8% and 63.3% reported by comparable maternity clinic-based studies in Nigeria ( 22 ) and Russia ( 23 ) respectively. However, school-based survey on females reported lower awareness level of 30% in Nigeria ( 24 ) and 43.2% in South Africa ( 25 ). The disparity in awareness between maternity clinic-based and school-based studies could be attributed to public perspectives that adolescents and young female respondents in school-based studies are not matured enough for discussions relating to sexual activity as reported in previous studies ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Out of 200 known HPVs, at least 40 of them spread through sexual contact ( Oluwole et al, 2019 ). While many HPVs establish an infection that is cleared by the host immune system, small types are the most concerning since they are linked to cancer development ( Mushasha et al, 2021 ; Tesfaye et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Out of 200 known HPVs, at least 40 of them spread through sexual contact (Oluwole et al, 2019). While many HPVs establish an infection that is cleared by the host immune system, small types are the most concerning since they are linked to cancer development (Mushasha et al, 2021;Tesfaye et al, 2019). Almost all cases of cervical cancer are caused by HPV with certain types also causing cancers of the vulva, and vagina in females, penile in males, and anal and oropharyngeal cancer in both females and males (Maharajan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%